2015
DOI: 10.3389/fmicb.2015.00177
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of thermophiles in a Malaysian hot spring determined using 16S rRNA and shotgun metagenome sequencing

Abstract: The Sungai Klah (SK) hot spring is the second hottest geothermal spring in Malaysia. This hot spring is a shallow, 150-m-long, fast-flowing stream, with temperatures varying from 50 to 110°C and a pH range of 7.0–9.0. Hidden within a wooded area, the SK hot spring is continually fed by plant litter, resulting in a relatively high degree of total organic content (TOC). In this study, a sample taken from the middle of the stream was analyzed at the 16S rRNA V3-V4 region by amplicon metagenome sequencing. Over 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 70 publications
11
123
1
3
Order By: Relevance
“…In general, SK is a shallow and fast-flowing stream with temperatures of 75-85°C and pH 8.0. Samples retrieved from this area were studied through 16S rRNA gene profiling (Chan et al 2015). This approach led to the identification of 83 phyla among which the predominant were Firmicutes, Proteobacteria, Chloroflexi, Bacteroidetes, Euryarchaeota and Crenarchaeota.…”
Section: Sungai Klah Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…In general, SK is a shallow and fast-flowing stream with temperatures of 75-85°C and pH 8.0. Samples retrieved from this area were studied through 16S rRNA gene profiling (Chan et al 2015). This approach led to the identification of 83 phyla among which the predominant were Firmicutes, Proteobacteria, Chloroflexi, Bacteroidetes, Euryarchaeota and Crenarchaeota.…”
Section: Sungai Klah Malaysiamentioning
confidence: 99%
“…Interestingly, by studying sequence affiliations the authors could highlight a relationship between the population diversity and the geochemical parameters within the hot spring. Moreover, it was shown that microbial communities were able to survive by exploiting different symbiotic strategies to prosper under multiple environmental stresses (Chan et al 2015). …”
Section: Sungai Klah Malaysiamentioning
confidence: 99%
“…Similar observations have been made by [13,14] that geographic locations play a significant role in bacterial community structure. Proteobacteria has also been reported from many studies based on the 16SrRNA analysis of hot springs with moderately high and very high temperatures (44-110°C) at various geographical locations, including India [15][16][17]. Since, Proteobacteria have been found in other hot spring studies including Indian hot springs, and was also one of the abundant taxa in this study, it appears to be indigenous to this region.…”
Section: Resultsmentioning
confidence: 78%
“…Temperature is the main factor that shapes microbial communities in the hot springs with different locations (Miller et al 2009). Notable similarity was observed in the involvement of different community members in methane metabolism in Attri as well as in Malaysian hot springs (Chan et al 2015).…”
Section: Discussionmentioning
confidence: 96%